Intelligent ubiquitous network - TONG Xiao-yu; ZHANG Yun-yong; XU Lei (Tongxin xuebao)
The first overview of ubiquitous computing,cloud computing and ubiquitous network technology was made.Then a new concept of Intelligent ubiquitous network,its concrete realization of the distributed intelligent open system and business data system were proposed.Finally,the network topology,architecture and key technologies of DIOS were discussed in detail.Intelligent ubiquitous network is the trend of future telecommunication network and can provide "everywhere,all-powerful" service.